2016
DOI: 10.1039/c6ra01919f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric breakdown strength and energy storage density in lead-free relaxor ferroelectric ceramics prepared using transition liquid phase sintering

Abstract: Lead-free relaxor ferroelectric ceramics have been widely explored for high power energy storage applications because of their high polarization saturation and low remnant polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 61 publications
1
61
0
Order By: Relevance
“…On the basis of the above analysis, the high electric energy storage density W total can be attributed to a high dielectric breakdown strength (DBS) and a large polarization difference ( P s ‐ P r ) . Previous research reveals that a small grain size and dense microstructure lead to high DBS …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the above analysis, the high electric energy storage density W total can be attributed to a high dielectric breakdown strength (DBS) and a large polarization difference ( P s ‐ P r ) . Previous research reveals that a small grain size and dense microstructure lead to high DBS …”
Section: Resultsmentioning
confidence: 99%
“…Previous research reveals that a small grain size and dense microstructure lead to high DBS. 43 To investigate the properties of the energy storage, the P-E hysteresis loops of the KNN-xSZN ceramics are measured at room temperature, and the results are shown in Figure 7A. The ceramics with Sr(Zn 1/3 Nb 2/3 )O 3 doping exhibit slim hysteresis loops, which is a characteristic of relaxor-like behavior.…”
mentioning
confidence: 99%
“…Because of the ever increasing complexity of the electronic devices, there is a strong demand for materials with multiple functions. Recently, lead‐based antiferroelectric (AFE) materials, as a kind of potential multiple functional electronic materials, have attracted great attention for their potential applications in high‐energy‐storage capacitors, microactuators, pyroelectric security sensors, cooling devices, multiferroic heterostructures, and pulsed power, owing to their unique electric‐field‐induced phase switching process . Currently, the studies on lead‐based AFEs are mainly focused on the bulk ceramics and thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lead-based antiferroelectric (AFE) materials, as a kind of potential multiple functional electronic materials, have attracted great attention for their potential applications in high-energy-storage capacitors, microactuators, pyroelectric security sensors, cooling devices, multiferroic heterostructures, and pulsed power, owing to their unique electric-field-induced phase switching process. [1][2][3][4][5][6] Currently, the studies on lead-based AFEs are mainly focused on the bulk ceramics and thin films. It is well-known that the low electric breakdown field for the bulk ceramics often leads to inferior final properties, such as small energy-storage density and low cooling coefficient.…”
mentioning
confidence: 99%
“…A large W R of $2.6 J/cm 3 and a moderate η of $ 73.2% have been achieved with an electric field of 400 kV/cm. 73 Later on this group designed a new 0.9(K 0:5 Na 0:5 ÞNbO 3 -0.1Bi(Mg 2=3 Nb 1=3 ÞO 3 composition to control grain size and enlarge saturated polarizations. Results demonstrated that a giant W R of $ 4.08 J/cm 3 with η of $ 63% existed under an electric field of 300 kV/cm.…”
Section: Energy Storage Performance In Ecofriendlymentioning
confidence: 99%